2015
DOI: 10.1002/bab.1376
|View full text |Cite
|
Sign up to set email alerts
|

Molecular cloning and transgenic characterization of the genes encoding chalcone synthase and chalcone isomerase from the Tibetan herbal plant Mirabilis himalaica

Abstract: Mirabilis himalaica is an endangered medicinal plant species in the Tibetan Plateau. The two genes respectively encoding chalcone synthase (MhCHS) and chalcone isomerase (MhCHI) were isolated and characterized from M. himalaica. The sequence analysis revealed that the two genes were similar with their corresponding homologous genes in other plants. The tissue profiles showed that both MhCHS and MhCHI had higher expression levels in roots than in stems and leaves. Transgenic hairy root cultures respectively wit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
9
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
4
2

Relationship

2
4

Authors

Journals

citations
Cited by 13 publications
(10 citation statements)
references
References 36 publications
1
9
0
Order By: Relevance
“…Therefore, researchers should pay increased attention to the biosynthesis of rotenoid in M. himalaica . In M. himalaica , rotenoid is primarily derived from the isoflavonoid biosynthesis pathway (Lan et al 2016 ). However, the detailed steps of rotenoid biosynthesis remain largely unknown.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Therefore, researchers should pay increased attention to the biosynthesis of rotenoid in M. himalaica . In M. himalaica , rotenoid is primarily derived from the isoflavonoid biosynthesis pathway (Lan et al 2016 ). However, the detailed steps of rotenoid biosynthesis remain largely unknown.…”
Section: Discussionmentioning
confidence: 99%
“…5 ). CHS and CHI play important roles during the upstream catalysis of rotenoid, but some critical nodes remain largely unknown (Lan et al 2016 ). In the present study, the combined analysis of the transcriptomic and metabolic profiles of M. himalaica indicated that some metabolites downstream of naringenin chalcone metabolism were produced in types and amounts more than those involved in rotenoid biosynthesis from isoliquiritigenin.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…It is possible that the metabolic activities of M. himalaica are significantly enhanced under the UV-B radiation, and M. himalaica adapts to UV-B radiation by increasing the ultraviolet-absorbing substance. Rotenoid, an important medicinal active ingredient in M. himalaica , is one of the downstream products of flavonoid metabolism [ 58 , 59 ]. Previous studies on rotenoid have been focused extensively on its anti-cancer activity and the treatment of leukemia [ 60 , 61 , 62 ].…”
Section: Discussionmentioning
confidence: 99%